Global livestock research workshop. International Livestock Research Institute - Fitzhugh, H.A. (Japan International Research Center for Agricultural Sciences, 1998)
The International Livestock Research Institute (ILRI) has a global mandate for research to improve the productivity and sustainability of crop-livestock systems in developing countries. ILRI is one of the 16 centres supported by the Consultative Group on International Agricultural Research to which Japan is the major country donor. ILRI is expanding its research activities outside Africa with priority for expansion in Asia. Research emphasis on ruminant genetics, health and feed resources; on interdisciplinary crop-livestock systems and on livestock research training and informaiton services. ILRI works through collaboration with scientists from national agricultural research systems, advances research institutes and other international agricultural research centers. Financial support from Japan and the contributions of Japanese scientists are supporting ILRI and out partners to serve the important mission of improving smallholder livestock systems for the benefit of poor people in developing countries.